Computational pH Level of Liquid based on IoT to Support Industry 4.0 - Handoko Setyo Kuncoro (Jurnal Teknologi Proses dan Inovasi Industri, 2020)
This article discusses computational measurements study of pH levels for liquids to support industry 4.0 based on Internet of Things (IoTs). The main objective of this study is to be able to provide the data of  pH level of liquids (or other chemical solutions) in real time and simultaneously so that it has the potential to increase the speed and ease of managerial decision making, especially for chemical processes that are important to industry. The method used follows the industry 4.0 transformation phase sequence which is simplified in some research activities such as hardware installation, software installation, device programming and network programming. As a case study, it has been made a simple application for measuring pH levels in commercial bottled mineral water and natural clean water. This article will initially explain the utilization of the BPH-231 interface with a pH PE-03 probe from Lutron products as input data for the computational processes. Then we explain the computational method using SCILAB 5.5.2 software and XAMPP network applications using the PHP programming language. As specimen samples, it has been selected the boiled natural clean water from the Manglayang mountains near Bandung city, West Java and commercial mineral water of AQUA products. Analyses of IoT-based digital pH level measurements have shown more accurate and precise results than using conventional litmus paper standards. The overall results for both device installations and internet-based programmings are proven to provide realtime data measurements and can be accessed from various locations simultaneously so that they will make managerial decision making easier and faster.